1995
DOI: 10.1159/000119238
|View full text |Cite
|
Sign up to set email alerts
|

Mizolastine, a Novel Selective Histamine H<sub>1</sub> Receptor Antagonist: Lack of Sedative Potential on the EEG in the Rodent

Abstract: The sedative potential of mizolastine, a new, potent and selective antagonist of histamine H1-receptors, has been evaluated in the rodent with EEG techniques. In chronically implanted rabbits, sedation was observed in ECoG recordings after intravenous injection of terfenadine (1–10 mg/kg) and loratadine (0.3–3 mg/kg) but not after intravenous injection of astemizole or mizolastine (1–10 mg/kg). In freely moving implanted rats, mizolastine and cetirizine (10 mg/kg i.p.) did not modify the sleep-wakef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…also showed no significant effects on spontaneous EEG activity in rats 14 or cats, 2 respectively. In contrast with the above findings, when both loratadine (10 mg/kg) and terfenadine (10 mg/kg) were administered intravenously, they increased the total duration of slow‐wave sleep in rats 7 . In addition, in humans, not only drowsiness, but also behavioural changes (sedation, attention, memory and recognition) are produced by second‐generation histamine H 1 receptor antagonists 5,6 .…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…also showed no significant effects on spontaneous EEG activity in rats 14 or cats, 2 respectively. In contrast with the above findings, when both loratadine (10 mg/kg) and terfenadine (10 mg/kg) were administered intravenously, they increased the total duration of slow‐wave sleep in rats 7 . In addition, in humans, not only drowsiness, but also behavioural changes (sedation, attention, memory and recognition) are produced by second‐generation histamine H 1 receptor antagonists 5,6 .…”
Section: Discussionmentioning
confidence: 67%
“…showed no remarkable effect on EEG activity in rats 14 or on sleep–wakefulness pattern in cats 15 . Depoortere et al 7 . reported that cetirizine showed no sleep facilitation effects at a dose of 10 mg/kg, i.p., in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies in which sleep/wake staging was aided by recording electromyogram (EMG) tone, intraperitoneal administration of diphenhydramine [23,47] and pyrilamine [23] increased total sleep time in rats without reducing REM sleep. By contrast, 2 nd generation, non-brain penetrating antihistamines such as mizolastine [48], azelastine [44,49], clemastine [49], epinastine, ceterizine [46], and levocabastine [44] did not alter EEG patterns in rats. The distinction between non-sedating antihistamines such as epinastine and ceterizine, and sedating antihistamines such as ketotifen in rats appears to relate to the degree of receptor occupation of sedating antihistamines made possible by increased brain penetration [46].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…H 1 blockers should not possess sedative effects. Mizolastine does not have sedative potential on the EEG in the rodent [20]. The psychomotor and cognitive effects of mizolastine was compared to terfenadine, triprolidine and placebo in healthy volunteers [21].…”
Section: Mizolastinementioning
confidence: 99%